Electrical and thermoelectrical properties of undoped Bi2Te3-Sb2Te3 and Bi2Te3-Sb2Te3-Sb2Se3 single crystals - Jeon, H.-W.; Ha, H.-P.; Hyun, D.-B.; Shim, J.-D. (1991)
The thermoelectric properties and Hall effects of a number of undoped Bi2Te3-Sb2Te3 pseudo-binary and Bi2Te3-Sb2Te3-5%Sb2Se3 pseudo-ternary single crystal alloys grown by the Bridgman method were measured over the temperature range from 77 to 580 K. All of the alloys showed p-type extrinsic conduction and the analysis of the Seebeck coefficient and electrical conductivity in the extrinsic range indicated partial degeneracy at the lower temperatures. The Seebeck coefficient and energy gap of the pseudo-ternary alloy increased and the electrical conductivity decreased with the addition of Sb2Se3. It was proved by the Hall measurement that the carrier concentration increased with increasing amount of Sb2Te3, and decreased with the addition of Sb2Se3, while the Hall mobility was constant except for the Sb2Te3-rich region at room temperature. The scattering of carriers in these alloys can be expressed as acoustic-mode lattice scattering and two-phonon processes. The figure of merit shows a maximum at a carrier concentration of about 4.0 × 1019cm-3 at room temperature. ？ 1991.